Perceived ethnic discrimination, ethnic-racial socialization, and substance use among ethnic minority adolescents. Issue 1 (1st March 2022) - Nieri, Tanya; Ayón, Cecilia; Yoo, Min; Webb, Megan
Abstract: Perceived discrimination is a significant problem among ethnic minority adolescents and has been consistently linked to negative outcomes, including substance use, although few studies examine this relation with more than one time point. The present study adds to the literature by examining whether ethnic-racial socialization moderates the effects of perceived discrimination at time 1 on recent substance use six months later in a sample of ethnic minority, public high school students in Southern California. The results from analyses of survey data showed that perceived discrimination did not predict the likelihood of the outcomes, and they suggest that discrimination based on attributes other than ethnicity, such as immigration or documentation status, may be operating in the sample. Future research should simultaneously analyze effects of discrimination by type of attribute as well as level (e.g., intragroup, intergroup, and structural). With regard to ethnic-racial socialization in the multivariate models, cultural socialization was negatively related to the likelihood of the outcomes. Preparation for bias was positively related to the likelihood of the outcomes. Promotion of mistrust was not statistically significantly related to the likelihood of the outcomes. Although the socialization variables did not moderate the effect of perceived discrimination, they were clearly related to substance use in multiple ways, suggesting that future research continue to distinguish the effects of socialization by type to better understand how they can be addressed to optimize youth outcomes.